Costs and efficacy ofolanzapine and risperidone in schizophrenia - Mapelli, Vittorio (Farmeconomia. Health Economics and Therapeutic Pathways, 2007)
Introduction: schizophrenia is a serious and long lasting psychiatric disease. The new “atypical” antipsychotic drugs, introduced in the 90s, have substantially improved the effectiveness of medical treatments, compared to previous neuroleptic drugs. Nowadays they tend to be used as first choice drugs. The ddd cost of atypicals may differ by 20% and health authorities may have an incentive to deliver the less costly drug, especially if they are generic. However the various drugs show differential effectiveness rates and a rational choice should consider both cost and effectiveness. Objective: the purpose of this analysis is to review the existing evidence on cost-effectiveness studies of olanzapine and risperidone, the two most prescribed drugs in Italy. Six published studies were identified, but attention was focused on two articles that reported consistent and methodologically sound results. Results: most reviewed studies are cost-minimization analyses, since effectiveness indicators show no significant statistical difference between the two drugs, and are inconclusive since the results depend on the evaluation setting. However one observational retrospective study showed a significant severity reduction over 12 months for patients treated with olanzapine (-2.46 on HoNOS scale; p